Cerebral revascularization by EC-IC bypass in ischemic conditions of different etiologies - Forhad H Chowdhury; Mohammod Raziul Haque; Jalaluddin Muhammad Rumi; Maliha Hakim; Sharif Uddin Khan; Mainul Haque Sarker (Romanian Neurosurgery, 2020)
Background: Even after the failure of EC-IC bypass trial, EC- IC bypass can help many patients in preventing future stroke. Here we present a case series of patients with cerebral ischemia from different etiological modes who underwent EC-IC bypass with positive end results.